Nonlinear effects of body size and optical attenuation on Diel Vertical Migration by zooplankton. (29th December 2015) - Ohman, Mark D.; Romagnan, Jean‐Baptiste
Abstract: We adopt a trait‐based approach to explain Diel Vertical Migration (DVM) across a diverse assemblage of planktonic copepods, utilizing body size as a master trait. We find a reproducible pattern of body size‐dependence of day and night depths occupied, and of DVM. Both the smallest surface‐dwelling and the largest deeper‐dwelling copepods refrain from migrations, while intermediate‐sized individuals show pronounced DVM. This pattern apparently arises as a consequence of size‐dependent predation risk. In the size classes of migratory copepods the amplitude of DVM is further modulated by optical attenuation in the ocean water column because increased turbidity decreases encounter rates with visually hunting predators. Long‐term changes in the ocean optical environment are expected to alter the vertical distributions of many copepods and thus to affect predator‐prey encounters as well as oceanic carbon export.